A quasi-randomized controlled trial of the I-PLAN intervention to promote hearing aid use among first-time adult hearing aid users - Ismail, Afzarini Hasnita; Munro, Kevin J; Armitage, Christopher J.; Marsden, Antonia; Dawes, Piers (Trends in Hearing, 2020)
Abstract Trends in Hearing Volume 25: 1–13 !The Author(s) 2020 Article reuse guidelines: sagepub.com/journals-permissions DOI: 10.1177/2331216520969472 journals.sagepub.com/home/tia Suboptimal hearing aid use negatively impacts health and well-being. The aim of this study was to conduct a controlled trial of a behavior change intervention to promote hearing aid use. This study was a quasi-randomized controlled trial with two arms. A total of 160 first-time hearing aid users were recruited at their hearing aid fitting appointments. The control arm received standard care. In addition to standard care, the intervention arm received I-PLAN, which comprised (a) information about the consequences of hearing aid use/nonuse, (b) reminder prompt to use the hearing aids, and (c) an action plan. The primary outcome, measured at 6 weeks, was self-reported proportion of time the hearing aid was used in situations that caused hearing difficulty. Secondary outcomes were data-logged hearing aid use, self-reported hearing aid benefit, selfregulation, and habit formation. The results showed that the proportion of time the hearing aids were used in situations that caused hearing difficulty was similar in both groups. There were no statistically significant differences between groups in any outcome measure including data-logged hearing aid use. The relatively high levels of hearing aid use across research participants may have limited the potential for the intervention to impact on hearing aid use. Although the intervention materials proved acceptable and deliverable, future intervention trials should target suboptimal hearing aid users.